Exploration and optimization of conditions for quantitative analysis of lignans in Schisandra chinensis by an online supercritical fluid extraction with supercritical fluid chromatography system. Issue 14 (24th June 2019) - Dai, Zhuoshun; Xin, Huaxia; Fu, Qing; Hao, Hongyuan; Li, Qiang; Liu, Qiaoxia; Jin, Yu
Abstract: An online supercritical fluid extraction with supercritical fluid chromatography system could provide sequential extraction and quantitative analysis of lignans in Schisandra chinensis . Supercritical fluid extraction conditions were optimized at 15 MPa, 50°C, and 4 min with supercritical CO2 adding 1% methanol; the elution volume and flow rate were set at 6 mL and 2 mL/min to blow extract out of the tank completely. The split‐flow rate was confirmed at 2.5%, which determines injection volume and accuracy of quantitative detection. The factors having negative influences on supercritical fluid chromatography retention in the online system, including sample loading forms and backpressure settings, are discussed in the paper. At last, an extraction‐quantitative method for lignans in Schisandra chinensis was developed, which could be finished within 19.5 min. The total content percentage of four lignans (Schisandrin, Schisandrin A, Schisandrin B and Schisandrol B) in four batches was respectively measured to be 1.42, 1.54, 1.62, and 1.90%.